KONSEP MATEMATIKA PADA ALAT MUSIK TRADISIONAL BENGKULU DOL DAN TASSA - Elen, Indri; Masyita Ariani, Nyayu; Riwayati, Selvi; Ramadianti, Winda; Asmara, Adi (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Abstract This study seeks to uncover the mathematical concepts present in traditional musical instruments from Bengkulu. This study was conducted in three locations, namely the Muaro Raflesia Studio, the Malebero Art Studio and State Middle School 11 in the city of Bengkulu. The subject of this research is a cultural figure who preserves traditional Bengkulu musical instruments. Observations in this research were carried out through direct observation of Bengkulu traditional musical instruments. The creation of mathematical concepts for traditional Bengkulu musical instruments was conducted through observation, which was then deepened through interviews and documentation. Data analysis techniques involved collecting data, reducing data, presenting data, and drawing conclusions The results of this research show that traditional Bengkulu musical instruments contain mathe matical concepts, namely circles, triangles, kites and congruence. The findings of these mathematical concepts can be developed into open materials in middle school.